PENGEMBANGAN PANDUAN SOSIODRAMA UNTUK MENINGKATKAN NILAI PEDULI SOSIAL SISWA SMP - Hayuni, Rizka Rosida; Flurentin, Elia (Jurnal Kajian Bimbingan dan Konseling, 2016)
This development reaserch aims to produce sociodramas manual to increase the value of social care junior high school students theoretically and practically acceptable. This research method adapted the Borg and Gall procedural model covering the planning stage, the stage of product development and test phase of the product. Design test is test material experts and drama experts, potential users test products and test a small group. These products meet very precise criteria, very useful, very easy and very attractive to mean very feasible to use. It can be concluded that the guidelines have been grateful sociodramas theoretically and practically.